MEWUJUDKAN SEKOLAH DASAR BERBASIS LINGKUNGAN MELALUI APLIKASI “AQUA-VERT” DI SD NEGERI 1 BOBOSAN - Diana Retna Utarini Suci Rahayu (Dinamika Journal : Pengabdian Masyarakat, 2020)
Aqua-vert comes from the terms aquaponics and verticulture, the concept of integrated cultivation between fish maintenance and gardening which is done vertically using a recirculation system. This concept is an innovative, practical and economical creation because it does not require large tracts of land, saves water, has high aesthetic value, is productive, simple and easy to understand. The purpose of this activity is to increase understanding environment and love of the environment in elementary school students through the aqua-vert application. This activity was carried out at Bobosan I Elementary School, North Purwokerto Subdistrict, Banyumas Regency, using the following methods: theory was given orally, increased understanding and skills carried out through training, followed by mentoring for one month, evaluated and finally conducted demonstration plots. The results of the activity showed an increase in the understanding of the target audience about the benefits of aqua-vert for the surrounding environment.